2004
DOI: 10.1111/j.1365-246x.2004.02476.x
|View full text |Cite
|
Sign up to set email alerts
|

The 2003 Bam (SE Iran) earthquake: precise source parameters from satellite radar interferometry

Abstract: S U M M A R YDifferential radar interferometry provided high-quality near-field deformation data for the 2003 Bam earthquake and therefore strong constraints on its source parameters. The ruptured fault segments could be clearly detected by using a Sobel Edge Filter on the phase-unwrapped deformation field. The estimated total rupture length is about 24 km. More than 80 per cent of the seismic moment was released from its southern segment of about 13 km, where the slip reached a maximum of up to 270 cm resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 18 publications
2
57
2
1
Order By: Relevance
“…The main strike-slip dislocation in TALEBIAN et al (2004) is located approximately 5 km west of the previously-mapped Bam fault, while the surface projection of the secondary dislocation lies at a distance of about 10 km east of the main rupture. WANG et al (2004) used descending and ascending interferograms and constructed a source model based on three rectangular faults, rupturing a total length of about 24 km from south to north crossing the Bam city. WANG et al (2004) concluded that more than 80 percent of seismic moment was released from a new dislocation located 4-5 km west of the Bam fault dipping 80°E.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main strike-slip dislocation in TALEBIAN et al (2004) is located approximately 5 km west of the previously-mapped Bam fault, while the surface projection of the secondary dislocation lies at a distance of about 10 km east of the main rupture. WANG et al (2004) used descending and ascending interferograms and constructed a source model based on three rectangular faults, rupturing a total length of about 24 km from south to north crossing the Bam city. WANG et al (2004) concluded that more than 80 percent of seismic moment was released from a new dislocation located 4-5 km west of the Bam fault dipping 80°E.…”
Section: Discussionmentioning
confidence: 99%
“…WANG et al (2004) used descending and ascending interferograms and constructed a source model based on three rectangular faults, rupturing a total length of about 24 km from south to north crossing the Bam city. WANG et al (2004) concluded that more than 80 percent of seismic moment was released from a new dislocation located 4-5 km west of the Bam fault dipping 80°E. WANG et al (2004) found no evidence for secondary thrust dislocation as proposed by TALEBIAN et al (2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We derive the slip distribution from the co-seismic GPS data using the inversion code SBIF (sensitivity-based iterative fitting) proposed by Wang et al (2006). The technique used in this code is similar to the constrained gradient approach as used by Ward and Barrientos (1986) to minimize the misfit function under a priori constraints.…”
Section: The Gradient Methods With a Priori Constraintsmentioning
confidence: 99%